Cardiac troponin level elevations not related to acute coronary syndromes - Giannitsis, Evangelos; Katus, Hugo (Nature reviews. Cardiology, 2013)
One-fifth of acutely symptomatic patients admitted to an emergency department have elevated levels of cardiac troponins (cTn), but the majority do not have an acute coronary syndrome (ACS)Reasons for elevated cTn levels in acute or chronic non-ACS conditions are likely to be multifactorial, including myocardial ischaemia, ventricular strain, myocyte trauma, impaired renal clearance, and unknown mechanismsHigh-sensitivity assays for cTn can rule out non-ST-segment elevation myocardial infarction at an early stage in the diagnostic processThe result of a test for cTn levels should not be interpreted in isolation, but in the context of clinical findingsEven low levels of cTn can be prognostically important and associated with adverse outcomes in the absence of an ACS, and require investigation of the underlying causes
Gesehen am 10.02.2020